Research of High Temperature Problem of High-speed Shaft Bearing for MW-class Wind Power Increase Gearbox - Fugang Li Chengchen Zhuo Ran Li Yongkui Yang Yang Wang (Jixie chuandong)
In view of the high temperature of high speed shaft bearing， which often occurs in the speed increase gearbox of MW-class wind power， which causes the wind turbine fail to work normally， taking the gearbox with high temperature problem of high speed shaft bearing as the research object， the design analysis is carried out. Three factors affecting the high temperature of bearing are found， that is friction power loss of bearing Pbj， power consumption of lubricating oil Piol and air temperature in engine room Tc. Then， three factors are analyzed in detail to find the corresponding preventive measures. At the same time， the analyzed high temperature factors are used to check the high temperature unit of high speed shaft bearing in the operation of wind field. Finally， it is found out that the high temperature reason of bearing is the small clearance of bearing.